Bed management team with Kanban web-based application - Rocha, Hermano lexandre Lima (2018)
Objective: To measure the effectiveness of the bed management process that uses a web-based application with Kanban methodology to reduce hospitalization time of hospitalized patients. Design: Before–after study was performed. Setting: The study was conducted between July 2013 and July 2017, at the Unimed Regional Hospital of Fortaleza, which has 300 beds, of which 60 are in the intensive care unit (ICU). It is accredited by International Society for Quality in Healthcare. Population: Patients hospitalized in the referred period. Intervention: Bed management with an application that uses color logic to signal at which stage of high flow the patients meet, in which each patient is interpreted as a card of the classical Kanban theory. It has an automatic user signaling system for process movement, and a system for monitoring and analyzing discharge forecasts. Main Outcome Measures: Length of hospital stay, number of customer complaints related to bed availability. Results: After the intervention, the hospital’s overall hospital stay time was reduced from 5.6 days to 4.9 days (P = 0.001). The units with the greatest reduction were the ICUs, with reduction from 6.0 days to 2.0 (P = 0.001). The relative percentage of complaints regarding bed availability in the hospital fell from 27% to 0%. Conclusion: We conclude that the use of an electronic tool based on Kanban methodology and accessed via the web by a bed management team is effective in reducing patients’ hospital stay time.